FACTORS AFFECTING THE AFFECTING THE READINESS OF PP NO.71 TAHUN 2010 ABOUT GOVERNMENT ACCOUNTING STANDARDS (Case Study on Working Units in KPPN Malang’s Working Area) - syah, Ardian; Atmini, Sari (Jurnal Ilmiah Mahasiswa FEB, 2012)
The purpose of this research is to analyze factors affecting the readiness of application of accrual-based government accounting standards at working unit level. This study was motivated by the  issuance of PP 71 of 2010 about Government Accounting Standards which will be implemented in 2015. This research is conducted on 160 working units  in KPPN Malang’s working area by using questionnaires. Data used in this research was 118 data. The Independent variables in this research are human resources quality, organizational commitment, and communication. The dependent variable is the readiness of the application of accrual-based government accounting standards.  Multiple linier regression analysis was applied to analyze the data. The statistical results indicate that factors affecting the readiness of application of accrual-based government accounting standards are human resource quality and communication. While the organizational commitment, is not affecting the readiness of application of accrual-based government accounting standards.   Key words:  readiness of application of accrual-based government accounting standards, human resources quality, organizational commitment, and communication.